THE PREVALENCE OF CAROTID CALSIFICATION IN REGULAR HEMODIALYSIS PATIENTS - Herwindo Ahmad, Riri A. Muzasti & Syafrizal Nasution (International Journal of Research Science and Management, 2019)
Introduction: Chronic kidney disease (CKD) can develop into End Stage Renal Disease (ESRD) which requires regular hemodialysis. Vascular classification, a complication of ESRD, contributes to cardiovascular disease in CKD patients and associated with mortality in these patients. Increased Carotid Intima-Media Thickness (CIMT) is considered as a marker of classification process. Method: This study was a cross-sectional study at Rasyida Kidney Hospital Medan. Subjects was taken by consecutive sampling that met the inclusion criteria. A carotid ultrasonography was done to measure the thickness of carotid artery as a vascular classification. CIMT value > 1 mm indicates a carotid classification. Result: The results showed that CKD was most common in men, as many as 35 patients (50,7%). Based on the carotid ultrasonography examination performed, the prevalence of carotid classification were 28 (40,6%) subjects. In subjects with carotid classification, majority of patients were men, as many as 16 (57,1%). Subjects with hypertension and overweight-obesity Body Mass Index (BMI)were associated with the prevalence of carotid classification (p= 0,009; p= 0,039). Conclusion: The prevalence of carotid calsification is more common in men. Hypertension and overweightobesity patients are associated with the prevalence of carotid classification